Василий Морозов - Ковычева Елена Ивановна (Удмуртия, 2013)
Экземпляры: ЦБ (20170904) / Инвентарный номер: 49171 / Цена: 100.00 / Сис.шифр: 85.143(2Рос.Удм) / Авт.знак: М 80 / ГРНТИ: 18.31.31 / ББК: 85.143(2Рос.Удм)